Surgical removal of an embolized Amplatzer septal occluder device from the right ventricle - Toktas, Faruk; Ozsin, Kadir; Kaymakci, Emre; Yavuz, Senol (The European Research Journal, 2015)
Atrial septal defect is one of the most common congenital heart defects encountered in adults. Currently, transcatheter atrial septal defect closure techniques have increasingly gained wide popularity as an alternative to surgery in many centers. However, they are associated with severe procedural complications requiring immediate surgical intervention. Here, we report a 29-year-old male patient with device embolization due to the migration of Amplatzer septal occluder device to the right ventricle at an early stage following percutaneous intervention. He underwent an emergency operation because of hemodynamic deterioration. The device was successfully removed with surgery and atrial septal defect was closed with a pericardial patch. The postoperative course was uneventful, and he was discharged from hospital on postoperative day 5.